tersebut PENGGUNAAN JURNAL REFLEKTIF MENULIS DALAM MENGAJAR MENULIS MELALUI METODE RECOUNT TEXT PADA STUDI KELAS KULIAH SMAN 1 PAGELARAN LAMPUNG - Rika Dartiara (Jurnal Pedagogy, 2017)
The research aims to analyze the process of using reflective journal writing through recount text at SMAN 1 Pagelaran and to analyze the students’ problems in writing reflective journal through recount text. This was a case study. The data were collected by observation, documentation, and interview. The research was conducted in SMAN 1 Pagelaran Lampung from July 31st 2015 to September 9th 2015. The participants involve in the reseach consisted of 32 students of X.2. In this case the researcher focused on six students. The process of teaching learning activity was conducted for six meetings. The result of this study showed that the process of using reflective journal writing in teaching writing through recount text in X.2 run well. The students’ writing task of reflective journal revealed that the use of reflective journal writing affected their writing.